Sustainability transitions in West African agriculture and food systems - El Bilali, Hamid; Cardone, Gianluigi; Rokka, Susanna; Falcis, Eleonora de; Naino Jika, Abdel Kader; Diawara, Ali Badara; Nouhou, Bassirou; Ghione, Andrea (2023)
Scientific evidence is crucial for the transition towards sustainable and resilient agri-food systems. However, sustainability transitions research has been so far north-biased and overlooked the Global South. This paper analyses the scholarly literature on sustainability transitions in West African agriculture and food systems. In particular, it investigates the bibliometrics and geographical coverage of the research field and explores whether and how it addresses topics such as transition frameworks, niches, food security and sustainability. The paper draws upon a systematic review of documents indexed in the Web of Science performed in July 2022. The low number of papers suggests that the research field is still marginal. The literature mainly deals with crop production whereas animal production and fisheries are generally overlooked. Only a few articles refer to a clear transition framework (e.g. Multi-Level Perspective). The addressed niches regard alternative agriculture systems (e.g. agroecology, agroforestry, climate-smart agriculture, conservation agriculture) and new agriculture techniques (e.g. irrigation). Food security and nutrition are still marginal topics in the research field. Sustainability transitions are argued to have positive environmental and socio-economic impacts. The promotion of research on sustainability transitions in West African agri-food systems is highly needed to address the multiple challenges that the region faces.